Health Risk Assessment on Exposure to Polycyclic Aromatic Hydrocarbon (PAHs) of Workers in Different Positions of Restaurants: A Case Study in Kitchens of Golf Clubs and Tourist Dams - Chaiklieng, Sunisa; Dacherngkhao, Thawatchai (Thai Journal of Toxicology, 2021)
Polycyclic Aromatic Hydrocarbon (PAHs) were gradually an important pollution problem from a cooking process which causes health impact and cancer. This study aimed to assess the health risk on exposure to PAHs of workers in different positions in restaurants by using a case study of kitchens of golf clubs and tourist dams. The concentrations of PAHs were monitoring from seven kitchens following NIOSH method 5515, and analyzed with Gas Chromatography-Mass Spectrometry (GC-MS). The carcinogenic risk assessment was calculated and a risk matrix was applied for occupational health risk assessment. The results showed that total PAHs average concentration of seven kitchens was 567.14±386.38 ng/m3 (150 - 1,020 ng/m3). The cancer risk assessment calculated from Benzo[a]pyrene exposure of different positions indicated an acceptable risk (<2.5 x10-6) which were highest in chef 3.82 - 6.62 x 10-12, followed by 3.43 - 4.97 x 10-12, 2.13 - 3.24 x 10-12 and 1.06 - 1.86 x 10-12 for the chef assistant, waitress, and cashier, respectively. The result was consistent with an assessment by the occupational health risk matrix that indicated an acceptable risk of all positions. The results recommend a health surveillance program for workers by application of occupational health risk assessment in a long term exposure to PAHs according to potential risk on exposure from cooking activities. Workers should be aware of Benzo[a]pyrene exposure and promoted awareness of self-protection with appropriate PPE use i.e. mask P95 to prevent fine dust and PAHs exposure while cooking and good ventilation design to reduce PAHs pollution.